18. Yüzyıldan günümüze sosyoloji bağlamında Ortadoğu tarım politikaları Biga örneği - Şahin, Şahika Sıdıka (My University, 2019)
21. yüzyılda tarım yeni dünya düzenindeki aktörlerin en fazla kontrol altına almak istediğialan olmuĢtur. IMF ve DB desteğiyle kontrol altına alınacak ülkeler (çevre) borçlandırılmaktave küresel sermaye bu çevre ülkelere serbestçe girebilmekte, tarımı ve tarım politikalarınıyönlendirebilmektedir. Küresel tarım Ģirketleri üretimden dağıtıma tüm ağı kontrol altındatutarak çevre ülke üreticileri üzerinde “bağımlı” yapılar oluĢturmaktadır.Bu noktadan hareketle yeni ekonomik düzende küresel tarım politikaları karĢısında Türkiyetarımı nasıl bir değiĢim ve dönüĢüm geçirmekteydi? Bu değiĢimin dinamiğininkavranabilmesi için süreç 18. Yüzyıldan günümüze kadar olan dönemi kapsamaktadır.Gelinen noktada Türkiye kırsalının somut bir örneği olan Biga üreticilerinin küresel tarımpolitikaları karĢısında değiĢen tarımsal üretim dinamiklerinin incelenmesi amaçlanmıĢtır. Bigajeopolitik öneminin yanında tarih boyunca bölge ekonomisinin de lokomotifi olmuĢtur.ÇalıĢmada derinlemesine görüĢme yöntemi kullanılarak gözlemlerde bulunulmuĢtur. ÇalıĢmahem teorik hem de pratik yöntemi gerektirdiğinden 18. Yüzyıldan baĢlanarak Türkiye‟nintarım politikaları süreci incelenmiĢtir.18. yüzyılın ve günümüzün uluslar arası belirleyicileri arasında karĢılaĢtırmalar yapılarakTürkiye tarım politikaları anlamaya çalıĢılmıĢ, benzerlikler tespit edilmiĢtir.Ülke gerçekliğiyle uyumlu tarım politikaları ortaya koyamayan, imzalanan uluslar arasıanlaĢmalar, tarımı ve tarımsal üreticiyi geri dönüĢü olmayan çıkmazlara sürüklemektedirler.Bu noktadan hareketle tezin ortaya koyduğu bir diğer tespit, uluslar arası anlaĢmaların küreselsermeye gruplarının çıkarlarıyla benzerlik gösterdiğidir. Bu noktada tarım kanunlarıdeğiĢtirilmiĢ, destekleme kapsamına çıkar gruplarının istediği ürünler konulmuĢtur.Ayrıca çalıĢma kapsamında akademik dünyaya, araĢtırmada elde edilen bulgularla küçüküreticilerin değiĢen tarım ve üretim paradigmasında kendilerini nasıl yeniden ürettikleriörneklerle sunulmuĢtur.Tarım, küçük üretici, neoliberal, Türkiye, Biga

ABSTRACTIn the 21st century, agriculture has been the field that the actors in the new world‟s orderdesired to control the most. With the help of IMF and WB, countries to be taken under controlhave been neigh boringly debited and the global capital can freely flow in to the nearbycountries and guide the agriculture and farm policies. Global farm companies generate„dependant‟ structures on the producers in the nearby countries by keeping the whole networkfrom production to distribution under control.Starting from this point, what kind of alterations and transformation has the agriculture inTurkey experienced in the face of the global farm policies in the new economical system? Theprocess that is needed to grasp the dynamics of this change involves the period starting fromthe 18thcentury until today. At this point, it is aimed to examine the drives of the changingagricultural production dynamics of Biga, which is an epitome of Turkey‟s countryside, in theface of global agricultural policies. Beside sits geopolitical importance, Biga has been alocomotive of the regional economy throughout the history.In this study, some observations are made by adopting the in-depth interview method. Thestudy examines the process of Turkey‟s farm policies from 18thcenturytotoday as itnecessitates both theoretical and practical methods.By making comparisons between international determinants of today and that of 18thcentury,it is aimed to understand Turkey‟s farm policies, and some similarities are detected.The signed international treaties which cannot put for the policies in line with Turkey‟sfactuality‟s lead the agriculture and agriculture producers into a dead end. From this point ofview, another finding in this thesis is that international treaties have commonalities with theinterests of the global capital groups. At this stage, the farm policies have been altered and theproducts which are desired by the interest groups have been included within the supportscope.Additionally, with the help of the findings of this study, the way how farmers regeneratethemselves with in the changing farm and production paradigms has been presented for thebenefits of the academia.
Keywords: Biga; Biga Agriculture; farmers; küçük üretici; neoliberal; neoliberals; Tarım; Turkey; Türkiye